HUBUNGAN AKTIVITAS FISIK DAN DURASI DUDUK TERHADAP NYERI LEHER PADA KARYAWAN KANTOR SELAMA WORK FROM HOME - Anggi Riyani Asri (2020)
Background: WFH makes employees have more time to rest, and do physical activity correctly, to assess physical activity used RAPA test, if physical activity is done in the wrong way it can cause neck pain, and make employees work within a short duration. Purpose: To find out whether or not there is a relationship between physical activity and the duration of sitting to neck pain complaints to employees during WFH. Method: Used with cross sectional design. The sample of this study was office employees from PT Margo Indonesia Service, who were selected according to inclusion and exclusion criteria totaling 45 people. Results: Bivariate correlation hypothesis test results with non-parametric test (spearman) obtained results in the from of a relationship between the numeric rating scale of the duration of sitting and RAPA test, with a value of RAPA1 p=0,765, RAPA2 p=0,404, and duration of sitting time p=0,408 where this result is not significant because p>0,05 and there is a correlation coefficient with a value of RAPA1 -0,045, RAPA2 0,128, and the duration of sitting time 0,126 where the results are very low. Conclusion: There is no relationship between physical activity and sitting duration for complaints of neck pain in office employees.